Exploring the integration of fish powder in school meal programs in Malawi through a food environment lens: acceptability, affordability, and convenience - Ahern, Molly; Lowore, Tijoy; Andrianarimanana, Mihasina Harinaivo; Banda, Amenye; Toppe, Jogeir; Ng’ong’ola-Manani, Tinna (Frontiers in Nutrition, 2025)
IntroductionDespite recognition that fish is a unique source of essential fatty acids, as well as bioavailable protein and micronutrients that are important for child and adolescent development, fish -and animal-sourced foods more broadly- are often not included in school meal programs in low- and middle-income countries in Sub-Saharan Africa. School meal programs have been promoted for decades for improving educational outcomes, such as reduced absenteeism and increased enrolment, but can also improve food security and nutrition of learners and livelihoods for local producers when foods are sourced locally. Even in countries where fish plays an important role in nutrition and food security, such as Malawi, where it provides 14.2% of available animal protein and employment for 217,000 people, it has not been featured in school menus.MethodsThe objective of this study was to explore the integration of fish products into school meal programs that source foods from local producers in Malawi, by assessing the quality, convenience and affordability dimensions of the school food environment. This was done by conducting 1) acceptability trials amongst schoolchildren aged 6-13 years, 2) assessment of time costs for processing fish powders and 3) ease-of-use for school volunteers to integrate fish powder into school meals, and 4) evaluation of the cost of production of fish powders and their affordability for school meal programs.ResultsWe found that fish powder incorporated into various school meal recipes were highly accepted, with approximately 90% of learners consuming over 75% of porridges containing pan-roasted fish powder, regardless of whether learners were from a lakeshore or inland district. This was further supported by the highest sensory ratings for attributes such as smell, taste, and appearance of porridges containing pan-roasted usipa powder. While pan-roasting the fish before grinding it into fish powder was more accepted by students, pan-roasting added processing time and costs (in relation to other processing methods) due to the need for fuelwood, raising concerns over economic and environmental sustainability.ConclusionAdding animal-source food to school menus is one pathway to fight malnutrition and ensure food security. Fish powder has great potential to contribute to this agenda through school meal programs and should be promoted as an ingredient in school meals in Malawi.